What are You Lookin' at? Aerial and Space Observation for Arms Control. (1st March 2021) - Koplow, David A.
Abstract : Effective arms control between rival states requires reconciling three autonomous elements simultaneously: a) politics—the substantive agreement about what military items and activities will be restricted or prohibited; b) technology—the means and methods to monitor compliance with those negotiated limitations; and c) law—the rights and obligations that enable effective international use of the designated verification capabilities. Each of these three variables changes over time; the history of arms control reveals the difficulty of keeping them in sync as international conditions evolve. Today, we are in a period of remarkably rapid revolution regarding all three factors—particularly evident in the air and space domains—which will generate exciting new opportunities and require negotiators to be extraordinarily deft and responsive. This essay reviews some illustrative prior state practice in arms control in harmonizing the three variables and speculates about future adaptations.